1993
DOI: 10.3354/dao017107
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and pathological effects of orally administered ivermectin in Atlantic, Chinook, and coho salmon and steelhead trout

Abstract: Because ivermectin (22,23-Dihydroavermectin B,) has been proposed as an oral treatment against sea lice infections of farmed salmonids, we investigated the toxicity and pathological effects of various doses of ivermectin administered orally every second day to steelhead trout Oncorhynchus mykiss, coho salmon Oncorhynchus kjsutch, chinook salmon Oncorhynchus tshawytscha and Atlantic salmon Salmo salar under laboratory conditions. These species differed in their ability to tolerate ivermectin, with coho salmon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Cumulative mortalities of 80 % and greater were reported for Atlantic salmon fed 3 doses of ivermectin at a targeted concentration of 0.20 mg kg-' fish, or 1 dose of ivermectin at targeted concentrations of 0.50 or 1.0 mg kg-' fish (Johnson et al 1993). Jackson & Costello (1992) report a tissue withdrawal time of 700 degree days and note that this limits its use to treatment of infections in smolts.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative mortalities of 80 % and greater were reported for Atlantic salmon fed 3 doses of ivermectin at a targeted concentration of 0.20 mg kg-' fish, or 1 dose of ivermectin at targeted concentrations of 0.50 or 1.0 mg kg-' fish (Johnson et al 1993). Jackson & Costello (1992) report a tissue withdrawal time of 700 degree days and note that this limits its use to treatment of infections in smolts.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al (1993) studied the pathological effects of various doses of the drug administered orally every second day to different species of salmonids and found that the species differed in their ability to tolerate ivermectin, with coho salmon Oncorhynchus kisutch being the most tolerant, followed by chinook O. tshawytscha and Atlantic salmon. It should be noted however that some of these fish were of different weight, and the experiments were not run at the same temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Resale or republication not permitted without written consent of the publisher salmon (Hoy et al 1990, O'Halloran et al 1992, Johnson et al 1993, Smith et al 1993, Kilmartin et al 1997, Palmer et al 1997) and rainbow trout (Halley et al 1989) this data is largely restricted to salmonids and does not include fish cultured at warmer temperatures.…”
Section: Abstract: Ivermectin · Sea Bass · Dicentrarchus Labrax · Tomentioning
confidence: 99%
“…Observations included scale color changes, aberrant swimming behavior, lethargy, and mortality. 6,10,15 If fish displayed severe changes such as paralysis or flared opercula, they were immediately euthanized.…”
Section: Observationsmentioning
confidence: 99%
“…6 Ivermectin is used to treat parasites in both aquatic and mammalian species. 7,8,10 It is effective for treating parasitic infestations through top-coating onto feed, but is not extensively used in aquaculture due to its narrow margin of safety. 6,11 This study had two goals.…”
Section: Introductionmentioning
confidence: 99%